Planning and Development of Burai Tourism Village in Ogan Ilir Regency, South Sumatra - Muhammad Halfi Indra Syahputra; Hanif Hasan (Brilliant International Journal Of Management And Tourism, 2025)
Burai Village in Ogan Ilir Regency, South Sumatra, holds significant natural, cultural, and traditional potential to be developed into a leading tourist destination. This study aims to identify planning and development strategies for Burai Village as a tourist destination using a descriptive exploratory approach. Data were collected through observation, interviews, and documentation, and analyzed using SWOT analysis, BCG matrix, and Ansoff matrix. The findings reveal that Burai Village possesses strengths such as unique cultural heritage, stunning natural landscapes, and traditional culinary attractions. However, it faces challenges including limited tourism attractions, inadequate facilities, and low community awareness of tourism. Development strategies include creating new attractions, improving village facilities, conducting human resource training, and implementing digital marketing promotions. These strategies are expected to enhance the village's tourism appeal, generate employment opportunities, and support local economic growth. The study provides a comprehensive guide for village tourism managers to optimize Burai Village's potential as a sustainable ecotourism destination.